Social responsibility among junior high school students - Mahfud, Ali; Hambali, IM; Setiyowati, Arbin Janu (Psychology, Evaluation, and Technology in Educational Research, 2025)
Character education in Indonesia plays a crucial role in shaping students to be well-balanced in both academic competence and social responsibility. Social responsibility is a fundamental human capacity to live in harmony within society, helping to maintain a balance between individual behavior and societal norms. The purpose of this study is to measure the percentage of each dimension of social responsibility at State Junior High School 1 Turen. This research employs a survey method, with data analyzed using descriptive analysis. The results of the percentage analysis for each dimension of social responsibility at State Junior High School 1 Turen, Malang, are as follows: (1) The dimension of self and others understanding scored 70.89%, which is categorized as fair. (2) The dimension of socialization scored 64.15%, categorized as low. (3) The problem-solving dimension scored 62.72%, also categorized as low. (4) The communication dimension scored 78.20%, categorized as good. (5) The sharing ability dimension scored 70.45%, categorized as fair. (6) The dimension of empathy and concern scored 65.84%, also falling under the fair category.